2017
DOI: 10.1111/jth.13784
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multiple electrode aggregometry with lumi‐aggregometry for the diagnosis of patients with mild bleeding disorders

Abstract: Background Multiple electrode aggregometry (MEA) measures changes in electrical impedance caused by platelet aggregation in whole blood. This approach is faster, more convenient and offers the advantage over light transmission aggregometry (LTA) of assessing platelet function in whole blood and reducing preanalytical errors associated with preparation of platelet-rich plasma (PRP). Several studies indicate the utility of this method in assessing platelet inhibition in individuals taking antiplatelet agents (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…We hypothesized that identification of threshold concentrations for agonists had the potential for improving sensitivity to mild/moderate platelet aggregation abnormalities, similar to LTA, where use of threshold concentrations is recommended . The agonist concentrations used for MEA in the present study are, therefore, lower than concentrations used in previous studies of normal controls or patients . The threshold concentrations for ADP, collagen, and TRAP used in the present study are similar to those identified by Toth et al, although the anticoagulant used for the present study was different (sodium heparin rather than citrate or hirudin).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…We hypothesized that identification of threshold concentrations for agonists had the potential for improving sensitivity to mild/moderate platelet aggregation abnormalities, similar to LTA, where use of threshold concentrations is recommended . The agonist concentrations used for MEA in the present study are, therefore, lower than concentrations used in previous studies of normal controls or patients . The threshold concentrations for ADP, collagen, and TRAP used in the present study are similar to those identified by Toth et al, although the anticoagulant used for the present study was different (sodium heparin rather than citrate or hirudin).…”
Section: Discussionsupporting
confidence: 60%
“…As no patient had a confirmed diagnosis of a platelet function disorder at enrollment, the purpose of this study was not to identify the utility of either method in the identification of specific platelet function abnormalities, as described by Al Ghaithi et al . In contrast to Al Ghaithi's study, we found more patient samples with abnormal MEA responses than with abnormal LTA responses, including patients who had more than one abnormal agonist response: 28% (MEA) vs 15% (LTA).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Although LTA has shown to be useful for the detection of platelet function disorders in women with HMB, it has the disadvantage that many hospitals do not have access to a laboratory, which is using LTA. Furthermore, many laboratories have stopped using LTA, because it is time‐consuming; it requires large blood volumes to prepare platelet rich plasma and needs to be performed on freshly collected blood samples . In addition, it requires expert laboratory skills, it needs dedicated equipment, and it has a high intra‐ and interbatch and technician variability within and between tests .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many laboratories have stopped using LTA, because it is time‐consuming; it requires large blood volumes to prepare platelet rich plasma and needs to be performed on freshly collected blood samples . In addition, it requires expert laboratory skills, it needs dedicated equipment, and it has a high intra‐ and interbatch and technician variability within and between tests . In this study, we have used agonist‐induced platelet activation measured in whole blood .…”
Section: Introductionmentioning
confidence: 99%